Sunny - Matsumoto, Taiyo, 1967- (VIZ Media, LLC, 2013)
"The story of an orphanage, the children who live in it, and the beat-up old Nissan Sunny 1200 which provides a trio of boys with a means of escape from their bleak everyday lives."--MangaHere.com review.